The Collective Work of Teachers for the Assessment of Learning as a Professional Norm? A Literature Review to Examine this Emerging Trend - Ochelen, Jean-Pascal; Yerly, Gonzague; Mottier Lopez, Lucie (Mesure et évaluation en éducation, 2024)
This paper presents a rapid review of the Anglophone and Francophone literature on collaboration among teachers to assess student learning. This kind of collective work tends to become a norm in education systems, raising major issues in the field of educational assessment. The literature already contains summaries of empirical research dealing with teacher collaboration in general, but none dealing specifically with collective assessment practices. A systematic literature search led to the selection of 30 articles, in primary and secondary education. Analysis of these articles allows us to 1) identify the dynamics at work in the schools and 2) observe the consequences for all those involved in the school. The results allow us to discuss certain tensions linked to this trend, from the point of view of steering policies, but also about individual and collective evaluation practices.